To evaluate lower extremity ulcer cases in respect of their aetiological basis - A, Gajjam Shrinivas; Amol, Wagh (International Surgery Journal, 2017)
Background: Lower extremity ulcer is most common in our population due to their chronicity. Lower extremities are exposed to injury and having a circulation strained by upright posture. This has reason for researchers and surgeon who have been concerned with the reasons for their common occurrence and difficulty in their cure. Researcher interested to study the lower extremity ulcer cases in respect of their aetiological basis. Methods: 100 patients of lower extremity ulcer with various types were admitted in surgical wards of Mallareddy Institute of Medical Sciences, Hyderabad during study period. The cases were examined in detail and investigated thoroughly. If there is clinically doubtful case, the diagnosis was made only after histopathological examination. Results: Most common type of ulcer was found in the present was venous 25 (25%) cases, contributed by male (21) and female (04) followed by diabetic 22 (22%) and Traumatic 18 (18%). Most of cases belongs to the age group 41-60 years (45) and male (37 cases). High saphenous vein ligation with stripping of veins (21.4%) and conservative (21.4%) treatment were common surgical procedures used for the treatment of Venous ulcer. Conclusions: In the present, Venous ulcers are the most common of all leg ulcers with high morbidity. The surgical procedures are directed at prevention of venous reflux at various levels.